In detention, repeating the year, or expelled? Perspectives for the realisation of the Constitutional Treaty - Andreas Maurer (Stiftung Wissenschaft und Politik (SWP), 2006)
The negative results of the referenda on the Treaty establishing a Constitution for Europe (ECT) in France and the Netherlands have thrown the European Union into a deep crisis. The options should be carefully and unemotionally weighed up.Should the EU collectively "put itself in detention" in order to improve or complement the Treaty? Or will it plump for "repeating the year", attempting on the basis of the Treaty of Nice to pursue individual reforms from the ECT in a sub-constitutional manner? Or is an "expulsion" thinkable, whereby those states unwilling to ratify the ECT separate themselves from an EU regulated by the ECT?The self-decreed delay is risky. The success of such a strategy depends largely upon the readiness of Europe's heads of state and government to stick with the political and institutional reforms aimed at in the ECT. A decision in favour of the status quo could entail the EU's relegation to the international league of state systems that are not able - or prepared - to reform themselves. This option can only bring success if the European actors resolutely push for the implementation of the reforms in the ECT which, after all, were agreed to among parliaments, government representatives and a large part of civil society. The withdrawal or exclusion of all those states which are not ready to take up the ECT certainly appears politically inopportune at the present time. All the same, this option should not be ruled out at this stage of the debate. Even if this option would spell a rather painful process for all parties involved, it would be foolhardy to disregard it. Only towards the end of the ratification process will it become clear, whether and to what degree new chances have been created for the harmonious coexistence of various models of integration. (SWP-Research Papers / SWP)
Keywords: 320